EMOTION IN VISUAL DESIGN: A REVIEW - Anglay, Hemang Madhusudan (ShodhKosh: Journal of Visual and Performing Arts, 2023)
An artwork or visual design creates an impact on the minds of the viewer. It makes us think about a particular topic or subject. This research explores the psychological with respect to physiological understanding of emotional responses. It also tries to understand the behavioural changes which emotion can bring and is associated with creation of Visual Design. This study of various perspectives in the area of emotional connection and relation building will be a guiding resource for artists, designers as well as researchers.